2007
DOI: 10.1021/np060596p
|View full text |Cite
|
Sign up to set email alerts
|

Zooxanthellamide D, a Polyhydroxy Polyene Amide from a Marine Dinoflagellate, and Chemotaxonomic Perspective of the Symbiodinium Polyols

Abstract: A long-chain polyhydroxy polyene amide, zooxanthellamide D (ZAD-D, 1, C54H83NO19), was isolated from a cultured marine dinoflagellate of the genus Symbiodinium. ZAD-D (1) is a polyhydroxy amide consisting of a C22-acid part and a C32-amine part and furnishes three tetrahydropyran rings and six isolated butadiene chromophores. The relative stereochemistry of the tetrahydropyran ring systems was elucidated by NMR techniques. This metabolite showed moderate cytotoxicity against two human tumor cell lines. A phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…The vicinal coupling constants of H-) are not clarified a chair conformation. Instead, these values are agree well with those reported for a twist-boat conformation for 1[32] suggesting the steric effect of the bulky groups. In addition, the NOE correlations between H--5/H-6 (Fig.…”
supporting
confidence: 90%
“…The vicinal coupling constants of H-) are not clarified a chair conformation. Instead, these values are agree well with those reported for a twist-boat conformation for 1[32] suggesting the steric effect of the bulky groups. In addition, the NOE correlations between H--5/H-6 (Fig.…”
supporting
confidence: 90%
“…It is important to note that zooxanthellae of the genus Symdiodinium, which live in symbiosis with the hydrocorals, produce large polyhydroxylated secondary metabolites, namely, zooxanthellatoxins Nakamura et al, 1993) and zooxanthellamides (Onodera et al, 2004;Onodera et al, 2005;Fukatsu et al, 2007) that are of interest due to their characteristic structure and potent vasoconstrictor activity. Recently, we found indirect evidence that the hydrocorals, not the symbiotic zooxanthellae, are the source of the vasoactive compounds present in the M. complanata aqueous extract, since we demonstrated that the extract prepared from bleached specimens displayed concentration-dependent vasoconstrictor effects that were not significantly different from those induced by the extract obtained from the control specimens .…”
Section: Discussionmentioning
confidence: 99%
“…ZAD-D is a linear polyhydroxylated polyketide and has been reported from Symbiodinium strain JCUCS-1 [ 45 ]. It is related to amphidinols isolated from the dinoflagellate, Amphidinium sp.…”
Section: Discussionmentioning
confidence: 99%
“…It is related to amphidinols isolated from the dinoflagellate, Amphidinium sp. [ 45 ]. This molecule is a polyhydroxy amide consisting of a C 22 -acid moiety and a C 32 -amine moiety; it furnishes three tetrahydropyran rings and six isolated butadiene chromophores.…”
Section: Discussionmentioning
confidence: 99%